Differential activation of target cellular promoters by p53 mutants with impaired apoptotic function. - Ludwig, R L (1996)
The p53 tumor suppressor protein is a sequence-specific transcriptional activator, a function which contributes to cell cycle arrest and apoptosis induced by p53 in appropriate cell types. Analysis of a series of p53 point mutants has revealed the potential for selective loss of the ability to transactivate some, but not all, cellular p53-responsive promoters. p53 175P and p53 181L are tumor-derived p53 point mutants which were previously characterized as transcriptionally active. Both mutants retained the ability to activate expression of the cyclin-dependent kinase inhibitor p2lcip1/waf1, and this activity correlated with the ability to induce a G1 cell cycle arrest. However, an extension of this survey to include other p53 targets showed that p53 175P was defective in the activation of p53-responsive sequences derived from the bax promoter and the insulin-like growth factor-binding protein 3 gene (IGF-BP3) promoter, while p53 181L showed loss of the ability to activate a promoter containing IGF-BP3 box B sequences. Failure to activate transcription was also reflected in the reduced ability of the mutants to bind the p53-responsive DNA sequences present in these promoters. These specific defects in transcriptional activation correlated with the impaired apoptotic function displayed by these mutants, and the results suggest that activation of cell cycle arrest genes by p53 can be separated from activation of genes with a role in mediating the p53 apoptotic response. The cellular response to p53 activation may therefore depend, at least in part, on which group of p53-responsive genes become transcriptionally activated.